Study on awareness, knowledge, and practices towards antibiotic use among the educated and uneducated people of Khyber Pakhtunkhwa Province, Pakistan - Javed, Shahzeb; Ahmad, Junaid; Zareen, Zainab; Iqbal, Zahid; Hubab, Muhammad; Rehman, Mujaddad Ur; Shakeela, Qismat; Khan, Ibrar; Hayat, Azam; Ahmed, Shehzad (ABCS Health Sciences, 2023)
Introduction: Antimicrobial resistance developed through the inadequate use of antibiotics; is an overriding task for global public health. Objective: To explore awareness, knowledge, and practices, and compare the elements associated with antibiotic misuse in different University students and uneducated people of Khyber Pakhtunkhwa Province, Pakistan. Methods: Cross-sectional study was conducted from July to December 2020 using a validated questionnaire. Data were collected from eleven different university students and uneducated people of Khyber Pakhtunkhwa, Pakistan. Results: 3,600 questionnaires were completed, consisting of 56.9% Male and 43.0% Female. 1,999 (55.5%) of the antibiotic users reported through the survey used non-prescription antibiotics within a one-month study period. Out of the participants, 230 (6.3%) were uneducated or their education level was below matric rest were university students. 1999 (55.5%) reported buying Antibiotics with Medical Prescription. Most self-medicated participants (56.9%) stop taking antibiotics when they feel better. More than 90% of the respondents answered that doctors and pharmacist staff do not guide them well that how to use antibiotics. 2,171 (60.03%) respondents mistakenly believed that antibiotics improve restoration from coughs and colds. Only 720 (20%) respondents knew that antibiotics also disturb normal flora and 547 participants (15.9%) agree that unnecessary use of antibiotics causes bacterial resistance. Conclusion: Finding from this study may have important implications for public health policy in Khyber Pakhtunkhwa, Pakistan given the growing global resistance to antibiotics and the reported health issues related to their improper use.